Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fmicb.2018.02204
|View full text |Cite
|
Sign up to set email alerts
|

A New Freshwater Cyanosiphovirus Harboring Integrase

Abstract: Pelagic cyanobacteria are key players in the functioning of aquatic ecosystems, and their viruses (cyanophages) potentially affect the abundance and composition of cyanobacterial communities. Yet, there are few well-described freshwater cyanophages relative to their marine counterparts, and in general, few cyanosiphoviruses (family Siphoviridae) have been characterized, limiting our understanding of the biology and the ecology of this prominent group of viruses. Here, we characterize S-LBS1, a freshwater sipho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 88 publications
1
31
0
Order By: Relevance
“…Phylogenetic analysis based on the large terminase subunit TerL showed that Mic1 falls into the "P22-like headful" cluster ( Figure 4A), which has a terminally redundant and circularly permuted genome (Casjens and Gilcrease, 2009). Mic1 is closely related to siphovirus Lactobacillus thermophilus prophage Lj964 (Desiere et al, 2000) and Staphylococcus aureus phage phiETA (Yamaguchi et al, 2000) based on the pac-site DNA packaging and long tail morphogenesis modules, but distinct from the λ-like freshwater cyanosiphophage S-LBS1 (Zhong et al, 2018).…”
Section: Genome Sequence Of Mic1mentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenetic analysis based on the large terminase subunit TerL showed that Mic1 falls into the "P22-like headful" cluster ( Figure 4A), which has a terminally redundant and circularly permuted genome (Casjens and Gilcrease, 2009). Mic1 is closely related to siphovirus Lactobacillus thermophilus prophage Lj964 (Desiere et al, 2000) and Staphylococcus aureus phage phiETA (Yamaguchi et al, 2000) based on the pac-site DNA packaging and long tail morphogenesis modules, but distinct from the λ-like freshwater cyanosiphophage S-LBS1 (Zhong et al, 2018).…”
Section: Genome Sequence Of Mic1mentioning
confidence: 99%
“…Before Mic1, only 14 cyanosiphophages have been genomesequenced, including 11 marine and 3 freshwater cyanophages. To determine the degree of genomic variability between the cyanosiphophages, the heatmap was clustered based on Bray-Curtis similarity (Zhong et al, 2018) and compared the gene similarities between two phages ( Figure 5A). The cyanophages A-HIS1 and A-HIS2 of the unicellular cyanobacterium Acaryochloris marina (Chan et al, 2011), CrV-01T of the filamentous Cylindrospermopsis (Raphidiopsis) raciborskii (Martin et al, 2019), vB_NpeS-2AV2 of the filamentous nitrogen fixing cyanobacterium Nodularia sp.…”
Section: Evolutionary Analyses At the Genome Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Some major achievements in marine viromics include the identification of viruses infecting the dominant bacterioplankton lineages (53)(54)(55)(56), which have eluded cultivation-based efforts (57)(58)(59)(60). In freshwater systems, in addition to viruses that infect cyanobacteria (61)(62)(63)(64), which are relatively amenable to cultivation, several viruses that infect ubiquitous freshwater bacterioplankton lineages have been identified in the last few years, including isolated viruses that infect LD28 (Ca. Methylopumilus) (44) and Comamonadaceae (65), and metagenomically-recovered viruses of Actinobacteria (66) and Polynucleobacter (67).…”
Section: Introductionmentioning
confidence: 99%
“…Again, these Group IV and V viruses also showed no sequence similarities with known viruses in the current databases (Figs 3 and 7). It is worth to note that two freshwater Synechococcus viruses (S-LBS1 and S-CRM01) were shown to cluster together with marine cyanoviruses and not with other freshwater cyanoviruses (Dreher et al, 2011;Zhong et al, 2018). In addition, freshwater Synechococcus virus S-CBWM1 and S-EIV1 also shared more homologues with marine counterparts S-TIM5 and S-CBS2, whereas they only showed partial sequence similarities of a few genes with Microcystis virus Mic1 and Cylindrospermopsis virus CrV-01T respectively (Figs 4 and 5).…”
Section: Distinctive Genomic Features Of Cyanoviruses Infecting Freshmentioning
confidence: 99%